Curiosity and Spatial Interest as Mediators of Conceptual Understanding and Learning Outcomes in Elementary Science Education - Wardana, Taufan Kusuma; Widodo, Wahono; Suryanti, Suryanti (Journal of Innovation and Research in Primary Education, 2025)
Curiosity and spatial interest are increasingly recognized as critical factors in improving science education at the elementary level. This study investigated the role of curiosity and spatial interest as mediators that bridge conceptual understanding and science learning outcomes. Employing a mixed-methods design, data were collected from 100 fifth-grade students and six teachers in three public elementary schools in Surabaya, Indonesia. Instruments included questionnaires, classroom observations, interviews, and concept comprehension tests. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined through thematic analysis. The results revealed that 70% of students with high curiosity demonstrated stronger conceptual understanding compared to their peers with lower curiosity levels. Exploration-based learning increased conceptual comprehension by 20%, while interactive media and direct experiments enhanced student engagement and understanding. Furthermore, 75% of students reported higher motivation during collaborative discussions, and 85% of students supported by parental involvement performed better in science learning. Spatial interest also emerged as a significant predictor of learning outcomes, as 68% of students who engaged in mapping and visualization activities achieved higher comprehension scores. This study concludes that curiosity and spatial interest are interrelated factors that substantially enhance science learning outcomes. Effective instructional strategies should integrate exploration, collaboration, interactive media, and spatial tasks to foster these elements. The findings contribute to the development of inquiry-based and contextual pedagogies that not only improve academic performance but also cultivate lifelong curiosity and ecological awareness among elementary students.